Topological Transition in a 3 nm Thick Al Film Grown by Molecular Beam Epitaxy. (27th December 2019) - Kumar, Ankit; Su, Guan-Ming; Chang, Chau-Shing; Yeh, Ching-Chen; Wu, Bi-Yi; Patel, Dinesh K.; Fan, Yen-Ting; Lin, Sheng-Di; Chow, Lee; Liang, Chi-Te
Abstract : We have performed detailed transport measurements on a 3 nm thick (as-grown) Al film on GaAs prepared by molecular beam epitaxy (MBE). Such an epitaxial film grown on a GaAs substrate shows the Berezinskii-Kosterlitz-Thouless (BKT) transition, a topological transition in two dimensions. Our experimental data shows that the MBE-grown Al nanofilm is an ideal system for probing interesting physical phenomena such as the BKT transition and superconductivity. The increased superconductor transition temperature (~2.4 K) compared to that of bulk Al (1.2 K), together with the ultrathin film quality, may be advantageous for future superconductor-based quantum devices and quantum information technology.